Determination of the linear attenuation coefficients of aluminum, iron and lead for collimated 661.66 keV gamma rays using TCS-172 gamma scintillation survey meter - Pham Dang, Quyet; Trinh, Thi Tu Anh (Communications in Physics, 2025)
Linear attenuation coefficients of Al and Pb for the 662 keV gamma rays have been carried out at the Training Center of Dalat Nuclear Research Institute using the Cs-137 source and the handheld equipment TCS-172 gamma scintillation survey meter. The gamma-ray beam emitted from the Cs-137 source was collimated with a narrow beam geometry. The results of our investigation were compared and found to be in good agreement with previously published data.